Integrating pattern matching and abstract interpretation for verifying cautions of microcontrollers. (19th August 2021) - Nguyen, Thuy; Tomita, Takashi; Endo, Junpei; Aoki, Toshiaki
Summary: Handling hardware‐dependent properties at a low level is usually required in developing microcontroller‐based applications. One of these hardware‐dependent properties is cautions, which are described in microcontrollers hardware manuals. The process of verifying these cautions is performed manually, as there is currently no single tool that can directly handle this task. This research aims at automating the verification of these cautions. To obtain the typical cautions of microcontrollers, we investigate two sections which have a considerable number of required cautions in the hardware manual of a popular microcontroller. Subsequently, we analyse these cautions and categorize them into several groups. Based on this analysis, we propose a semi‐automatic approach for verifying the cautions which integrates two static programme analysis techniques (i.e., pattern matching and abstract interpretation). To evaluate our approach, we conducted experiments with generated source code, benchmark source code, and industrial source code. The generated source code, which was created automatically based on several aspects of the C programme, was used to evaluate the performance of the approach based on these aspects. The benchmark and the industrial source code, which were provided by Aisin Software Co., Ltd., were used to assess the feasibility and applicability of the approach. The results show that all expected violations in the benchmark source code were detected. Unexpected but real violations in the benchmark programme were also detected. For the industrial source code, the approach successfully handled and detected most of the expected violations. These results show that the approach is promising in verifying the cautions. Abstract : This research proposes a semi‐automated approach for verifying the cautions of microcontrollers. The main idea is to integrate pattern matching and abstract interpretation techniques. The experiment results show that the approach was effective in handling an industrial source code.